Prescribed fire culture in the tallgrass & mixed-grass prairie of Kansas - Sulivant, Adrian L. (My University, 2025)
Human-prescribed fire, or the deliberate use of fire as a tool to shape landscapes, has been practiced for thousands of years. Within the past few centuries, the use of prescribed fire declined sharply. Prescribed fire has become a taboo for many communities in the United States due to the prominence of fire suppression policies adopted by the U.S. government. Despite prescribed fire’s benefits related to land conservation and reducing wildfire risk and intensity, many people still do not apply it. The purpose of this study was to explore pro-prescribed fire perceptions in two regions: the tallgrass ecoregion of eastern Kansas, where a culture of prescribed burning is prevalent, and the mixed-grass region of central Kansas where prescribed burning occurs but is less prevalent. Grounded theory guided the research. We used qualitative semi-structured interviews to collect data. In 2019, a separate research team interviewed 34 pro-prescribed fire ranchers in the tallgrass ecoregion of Kansas, one of the largest tracts of remaining native tallgrass prairie. In 2023, we analyzed and coded those interview transcripts as part of this study. During the spring to summer of 2024, I interviewed 15 pro-prescribed fire ranchers and key informants from the mixed-grass region of Kansas. We analyzed and coded mixed-grass participant transcripts in the same manner as the tallgrass group. Interview questions for both groups focused on motivations, demotivations, and challenges they faced in applying prescribed fire, as well as their perceptions of their communities’ attitudes toward prescribed fire. Once we finished coding all interviews, patterns emerged and were refined into themes, describing viewpoints held by the majority of participants in each of the two regions. A major motivation for most burners of both regions is the pragmatic need to maintain rangeland from invasive encroachment through the cost-effective use of prescribed fire. Risk is a major caveat to burners due to unexpected weather changes right before or during a burn, along with fear of liability from losing control of a prescribed fire and the potential for causing harm to life and property. In the tallgrass region, culture, tradition, and experience were important for the long-term prevalence of burning in the region. Most participants in the tallgrass region had decades of experience and exposure to fire across multiple generations, which helped to strengthen a long-term culture and pride in the preservation of land and profitability from the practice. Tallgrass rancher participants were highly motivated to control invasives, supported by their long-standing tradition of applying prescribed fire. For mixed-grass rancher participants and key informants, those who burn were highly motivated in countering invasive species encroachment in the region. In the mixed-grass region, key informants were highly motivated to and important in providing information about burning and coordinating with prescribed burn associations (PBAs). Mixed-grass burner participants diligently assessed and mitigated risks involved with burning. We recommend more qualitative and quantitative human dimensions of prescribed fire research be conducted, especially in the mixed-grass and short-grass ecosystems. Qualitative research should involve stakeholders who do not burn, such as county commissioners, to better understand outside perspectives in applying and promoting prescribed burning. There is a need to establish PBAs in communities without a recent history of prescribed fire, to include highly motivated leaders supported by state and federal agencies. There is also a need to support non-governmental organizations in providing education, equipment, and personnel to conduct burns in a safe and productive manner. Science-informed, long-term social practices of prescribed fire are vital in countering invasive species encroachment, supporting cost-effectiveness in agricultural operations, and preserving remaining grassland prairies.
Keywords: Fire culture; Fire; Prescribed fire; Culture; Agriculture; History